Species-specific gene regulatory network rewiring mediated by the GATA-type regulator NsdD in Aspergillus - Heungyun Moon; Mi-Kyung Lee; Junha Shin; Sung Chul Park; Julio C. Rivera Vazquez; Daniel Amador-Noguez; Nancy P. Keller; Hee-Soo Park; Kap-Hoon Han; Jae-Hyuk Yu (mBio)
ABSTRACT The evolutionarily conserved GATA-type transcription factor (TF) NsdD regulates sexual and asexual development as well as secondary metabolism in various Aspergillus species. Despite its well-known multifunctionality, the mechanisms by which NsdD coordinates such diverse biological processes remain unclear. To address this gap, we have conducted network-based multiomics analyses in two distantly related species, Aspergillus nidulans and Aspergillus flavus. Transcriptomic profiling reveals that NsdD regulates gene expression in a cell type- and species-specific manner. The potential evolutionary conservation of NsdD was tested by a cross-complementation experiment in which the A. nidulans nsdD gene was introduced into the A. flavus ΔnsdD mutant. This partially restored key phenotypes and gene expression profiles but failed to fully recapitulate wild-type regulation, suggesting species-specific functionality. To further dissect NsdD’s roles, we have performed genome-wide ChIP-seq analyses and identified 502 and 674 potential direct targets in A. nidulans and A. flavus, respectively, including major developmental and metabolic regulators such as veA, flbD, brlA, vosA, rosA, and laeA. Motif analysis reveals a conserved NsdD binding site (5′-GATCT-3′), designated as the NsdD response element. Network analyses uncover core regulatory modules and reveal extensive gene regulatory network (GRN) rewiring between the two species. While NsdD governs conserved biological processes, divergence in its direct targets and downstream interactions contributes to species-specific traits, including differences in asexual morphology and production of sterigmatocystin/aflatoxin. This study provides the first genome-wide comparative map of NsdD-mediated GRNs in filamentous fungi and highlights how evolutionary rewiring allows a conserved TF to acquire distinct regulatory functions across species.IMPORTANCEMultifunctional TFs are central in coordinating development and metabolism in filamentous fungi. In this study, we systematically dissect the regulatory functions of NsdD, a highly conserved GATA-type TF in Pezizomycotina, using network-based multi-omics approaches in two distantly related species, A. nidulans and A. flavus. Our analyses reveal that NsdD governs fungal development and metabolism through species-specific GRNs, directly targeting key upstream regulators and genes involved in core cellular processes. These regulatory distinctions underlie the morphological and metabolic differences observed between the two species. Notably, our cross-species comparison uncovers extensive GRN rewiring, demonstrating how evolutionary divergence can reshape transcriptional networks even under conserved regulatory control. The resulting GRN maps offer a valuable framework for understanding gene regulation in Aspergillus and provide a foundation for broader studies on the evolution of transcriptional networks and conserved regulatory factors in filamentous fungi.